COGNITIVE BEHAVIOR THERAPY FOR HOARDING DISORDER: FOLLOW‐UP FINDINGS AND PREDICTORS OF OUTCOME. Issue 12 (26th November 2013) - Muroff, Jordana; Steketee, Gail; Frost, Randy O.; Tolin, David F.
<x xml:space="preserve">Abstract</x> Background A cognitive‐behavioral model of hoarding posits deficits in information processing, maladaptive beliefs about and attachments to possessions that provoke distress and avoidance, and positive emotional responses to saving and acquiring that reinforce these behaviors. A 26‐session individual cognitive‐behavioral therapy (CBT) based on this model showed significant reductions in hoarding symptoms and large effect sizes (Steketee et al.[1]). Methods The present study presents findings at follow‐up (up to 12 months), as well as predictors of outcome at posttreatment (n = 37) and follow‐up (n = 31). Results Significant improvements at post‐treatment were sustained at follow‐up with large effects, and Clinical Global Impression‐Improvement (CGI‐I) ratings by clinicians and patients at follow‐up indicated that 62 and 79% of patients were rated "much improved" or "very much improved, " respectively. The most prevalent patterns of outcome were improvement followed by stable gains or little improvement across all time points. Pretreatment severity of hoarding, overall clinical status, gender, perfectionism, and social anxiety were all associated with worse outcome. Only perfectionism and gender emerged as significant predictors after controlling for initial hoarding severity. Conclusions The present findings suggest general stability of individual CBT outcomes for hoarding and indicated that gender, perfectionism, and social anxiety may affect outcomes. More research on larger samples is needed to direct efforts to improve treatment for hoarding.